Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor - Amaliyah, Fany Nurizza; Raharjo, Teguh Budi; Yunita, Eva Anggra (Jambura Economic Education Journal, 2026)
This research analyzes the implementation of the tax amnesty initiative, income levels of taxpayers, public service accountability, and taxpayer motivation influence motor vehicle tax compliance in Tegal City. The technique used for data analysis is multiple linear regression analysis utilizing SPSS version 22, and the approach utilized is simple random sampling. The Slovin formula was utilized for sampling, and data was gathered from 400 respondents. This study aimed to assess the impact of the tax amnesty program's implementation, taxpayer income levels, accountability in public service, and taxpayer motivation on compliance with motor vehicle tax in Tegal City. The study's findings indicated that the tax amnesty program, taxpayers' income levels, accountability in public services, and taxpayer motivation positively influenced motor vehicle tax compliance at the Samsat Office in Tegal City.